2019
DOI: 10.4189/shes.17.45
|View full text |Cite
|
Sign up to set email alerts
|

Using ICT to enhance student engagement in physical education

Abstract: The purpose of this study was to examine a physical education class utilizing information and communication technology (ICT). In particular, it aimed to clarify the effects of visual feedback displaying the participants' heart rate (HR) on a monitor during endurance running. The participants comprised 45 (boys = 20, girls = 25) fifth-grade students enrolled in a Japanese elementary school in Osaka prefecture. The study compared the participants' HR when it was displayed on a monitor during their running and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Movies also deepen the PE learner's recognition of the movement (Azuma et al, 2004). Moreover, it has been reported that videos would enable understanding and sharing of movement or lead to appropriate skill acquisition in sports through visual feedback (Rohleder & Vogt, 2018;Shishido & Hashimoto, 2019). Tablet-type devices equipped with cameras allow the easy record and play of movies, and learners themselves are increasingly using these devices in physical education (PE) classes (Sinelnikov, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Movies also deepen the PE learner's recognition of the movement (Azuma et al, 2004). Moreover, it has been reported that videos would enable understanding and sharing of movement or lead to appropriate skill acquisition in sports through visual feedback (Rohleder & Vogt, 2018;Shishido & Hashimoto, 2019). Tablet-type devices equipped with cameras allow the easy record and play of movies, and learners themselves are increasingly using these devices in physical education (PE) classes (Sinelnikov, 2012).…”
Section: Introductionmentioning
confidence: 99%